Literatura macedońska dla dzieci (rekonesans badawczy) - Mojsowa‑Czepiszewska, Wesna (Paidia i Literatura, 2019)
This short study embraces both the first sprouts of the written Macedonian literature for children (somewhere around the second part of the 19th century), and the literary production which happens after the establishment of the contemporary Macedonian language, that is, after the 1945. Still, the main accent is on two newer books: Verses also Grow (И строфите растат) by Alexandar Kujundziski and Jump and Skip (Скокни прескокни) by Vasil Mukaetov which is a part of the refreshed reading list as an optional book for the Macedonian language lessons in the primary schools in Macedonia. Both authors put an emphasis exactly on a child’s sensitivity and such issues as character growth and maturation. In their books, they transfer the reader from childhood to adulthood unnoticeably and lightly. Their message is to help the little human in the complex process of his or her own comprehension and to show him or her that he or she are not alone in this process.